Final –ww in the Late Egyptian Orthography: A Linguistic Assessment - Kilani, Marwan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
Various words in Late Egyptian texts present a final sequence –ww that is absent in earlier attestations and does not have any obvious etymological justification. No systematic discussion of these –ww , and not explanation for their use, has been offered so far. The present paper aims at filling this gap through a systematic reassessment of the phonological characteristics of a comprehensive corpus of words displaying this marker –ww . The results suggest that this marker is related in function with the so called spacefillers discussed in Kilani 2017; in particular it appears to be added at the end of words characterized by a stressed back vowel adjacent to a labial consonant w , b , p , f or m , and possibly ˓. Some considerations about the possible underlying linguistic reality and the rational for the use of this marker are added at the end of the article. One instance of the marker –ww in a magic spell of P. BM EA 9997 IV, and its possible role in clarifying a potentially ambiguous pronunciation of the associated verb, is discussed in a final Addendum. An appendix with the reconstruction of the vocalization for the words that survive in Coptic is provided here. A second appendix with the whole corpus is provided as online supplement.